Nigerian Arabic Literature and Contemporary Forms of Literary Creativity: a New Discourse - Murtadha Abd. Salam Al- Haqiqi (Qismul Arab: Journal of Arabic Education, 2021)
This article focuses on tracing the path of contemporary Nigerian Arabic literature and presents a constructive critical vision of his creative endeavors based on an inductive and descriptive approach, in order to take the author's hand to the ideal method in artistic creativity and what is possible. crowning their efforts, knowing that literature is an idea and a style, both of which are subject to technical foundations and standards, especially that of literary literature and entertainment effectiveness. The study draws attention to what young Nigerian poets need from the creativity of living without relying on cheap shows. He also suggests keeping the art of presentation and thought over maqamat, which some young writers call for reviving, arguing that contemporary life requires communicative language, not an abandoned classic.